Synthesis and in vivo proof of concept of a BODIPY-based fluorescent probe as a tracer for biodistribution studies of a new anti-Chagas agent. Issue 13 (24th January 2017) - Rodríguez, Gonzalo; Nargoli, Javier; López, Andrés; Moyna, Guillermo; Álvarez, Guzmán; Fernández, Marcelo; Osorio-Martínez, Carlos A.; González, Mercedes; Cerecetto, Hugo
Abstract : A BODIPY-fluorophore based probe (1-BODIPY ) for compound1 was developed and investigated for its potential as in vivo tracer. Abstract : The potential use of amide-containing thiazoles, especially (2 E, 2 Z )-3-allyl-4-[(( E )-4-cinnamylpiperazin-1-yl)carbonyl]-2-[2-(( E )-3-(furan-2-yl)propenylidene)hydrazono]-2, 3-dihydrothiazole (1 ), as drugs for the treatment of Chagas disease has been recently described. The therapeutic application of1 requires further pre-clinical studies, including in vivo biodistribution. In this sense, a BODIPY-fluorophore based probe for this drug (1-BODIPY ) was developed and investigated for its potential as an in vivo tracer. The fluorescent tracer was synthesized, physicochemically and in vitro biologically characterised, and its in vivo biodistribution evaluated. The in vitro studies demonstrated that the fluorescent probe could simulate the in vivo behaviour of compound1 . Furthermore, the in vivo proof of concept showed that the1-BODIPY biodistribution involves organs that are associated with the parasitic disease. These findings allow us to establish future administration routes and regimens in the treatment of Chagas disease with1 .